2018
DOI: 10.33143/jhtm.v4i1.201
|View full text |Cite
|
Sign up to set email alerts
|

Perubahan Berat Organ Hati, Ginjal, Limfa, Otak, Lambung, Testis, Jantung dan Paru-paru Mencit yang Diberi Ekstrak Batang Sipatah-patah (Cissus quadrangula Salisb.)

Abstract: Masyarakat Aceh telah lama menggunakan tumbuh-tumbuhan sebagai obat-obatan. Tumbuhan-tumbuhan tersebut digunakan untuk berbagai penyakit seperti sakit perut, demam, batuk, patah tulang dan lain sebagainya. Penelitian ini bertujuan untuk mengetahui efek toksik melalui berat organ hati, ginjal, limpa dan otak mencit yang diberikan ekstrak batang Sipatah-patah. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL). Penelitian ini menggunakan empat perlakuan dan lima ulangan. Perlakuan berupa empat tingkatan dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…A comparable investigation utilizing sipatah-patah stem extract containing flavonoids found no significant variation in the liver weight of mice [21]. Another study utilizing nano herbs from Phaleria macrocarpa in rats with doses up to 1608.1 mg/kg BW/day found no significant variation in the hepatic weight of mice [16].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A comparable investigation utilizing sipatah-patah stem extract containing flavonoids found no significant variation in the liver weight of mice [21]. Another study utilizing nano herbs from Phaleria macrocarpa in rats with doses up to 1608.1 mg/kg BW/day found no significant variation in the hepatic weight of mice [16].…”
Section: Discussionmentioning
confidence: 95%
“…This is conceivable because the liver is a critical organ in the body's homeostatic processes, metabolism, and toxin detoxification, as well as its involvement in regulating endogenous and external xenobiotics [24]. The liver contains Kupferr cells, which phagocytize poisons and other foreign substances/objects [21,25]. Subchronic toxicity tests on rats using flavonoids in Parkinson's therapy evaluating body weight, haematology, clinical biochemistry, and histopathology found that using flavonoids from Safflower at doses of 100, 300, and 500 mg/kgBW/day did not create toxic consequences [26].…”
Section: Discussionmentioning
confidence: 99%
“…In the P3 group, the average dose of allopurinol 30mg/kg BW was 1.16 gr, a difference of 0.18 gr from the control group (Table 3). The liver is an important organ in the detoxification process or defense against various foreign substances, bacterial invasion, and toxins, so the liver weight can change due to substance intake (Ceriana et al, 2018). Liver weight can decrease may be due to exposure to allopurinol, which can liver cells undergo necrosis.…”
Section: Resultsmentioning
confidence: 99%